Item Analysis of Minimum Competency Assessment (AKM) Information Text Literacy Level 5 Biology Based on Pisa Framework Review (FMIPA UNNES, 2022)
Ideal condition of education field occurs when students' science and reading literacy fulfill the average international standards such as PISA and TIMSS. According to the 2018 OECD report, Indonesian students' science and reading literacy are at the lowest rank. Improvement of the assessment system from student evaluation using UN items to National Assessment using Minimum Competency Assessment (AKM) items has been attempted by the government, which can be accessed through the PUSMENJAR and PUSMENDIK web pages. Analysis of AKM simulation items is needed in an effort to review the feasibility of items and students' abilities in information text literacy. The purpose of the study was to analyze the characteristics of AKM items tested based on the review of the domains of science and reading literacy PISA qualitatively, to analyze the characteristics of AKM items tested in measuring student learning outcomes related to the literacy of information text on biology subject quantitatively, and to analyze students' abilities related to the literacy of information text based on the results of the AKM simulation test which was tested quantitatively. Type of research used is mixed method research with the research design is concurrent embedded design. The research respondents were 75 students of class X at SMA Islam Sultan Agung 1, SMA Kesatrian 2, SMA Teuku Umar, SMA Negeri 10 Semarang, and SMA Negeri 12 Semarang. Research instruments were 15 items of AKM level 5 biology simulation items with supporting data for student and teacher response questionnaires. For the quantitative analysis, the validity was estimated with the fulfillment of the criteria, includes MNSQ, ZSTD, and Pt Measure Corr outfit values. Determination of the item difficulty level and student ability level categories were based on the logit value obtained from the standard deviation. The qualitative analysis includes document study using the AKM simulation items along with the science and reading literacy framework PISA 2018. The results showed that the AKM simulation items tested had reached the entire domain of science and reading literacy PISA, but the items did not contain low and moderate aspects of the cognitive demands domain. Based on the item characteristic analysis using MINISTEP, for the item validity that S1, S2, S3 and S4 are categorized as valid, S5, S6, S7, S8, S9, S10, S11, S14, and S15 are categorized as valid with revisions, and S13 are categorized as discarded item. AKM simulation items tested had a test reliability of 0,81 with a good category. There are 2 items in the very difficult category, 4 items in the difficult category, 6 items in the medium category, and 3 items in the easy category. Person characteristic analysis in the form of the ability level of 75 students as respondents which had high ability to solve AKM simulation items for all types of item tested.